2012
DOI: 10.2174/1871527311201070937
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced Neuroinflammation and Radiation Somnolence Syndrome

Abstract: Cranial irradiation remains a standard treatment for malignant and benign brain diseases. Although this procedure helps to lengthen the life expectancy of the patient, the appearance of adverse effects related to radiation-induced injury is inevitable. Radiation somnolence syndrome (RSS) has been described as a delayed effect observed mainly after whole-brain radiotherapy in children. The RSS was first linked to demyelination, but more recently it has been proposed that the inflammatory response plays a primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 75 publications
0
32
0
Order By: Relevance
“…It has been reported that deficient neurogenesis following cranial irradiation of rats is not caused by irradiation itself, but rather by the neuroinflammatory response resulting from radiation-induced tissue damages [69]. Indeed, in rodents, irradiation of the head results in reactive gliosis by both astrocytes and microglia [70,71]. In line with this, a marked increase in the activation and proliferation of microglial cells was observed in the hippocampus after a single dose of 10 Gy irradiation and was sustained over several months [65,72,73].…”
Section: Myeloablation By Irradiation: Mechanisms Side Effects and Amentioning
confidence: 99%
“…It has been reported that deficient neurogenesis following cranial irradiation of rats is not caused by irradiation itself, but rather by the neuroinflammatory response resulting from radiation-induced tissue damages [69]. Indeed, in rodents, irradiation of the head results in reactive gliosis by both astrocytes and microglia [70,71]. In line with this, a marked increase in the activation and proliferation of microglial cells was observed in the hippocampus after a single dose of 10 Gy irradiation and was sustained over several months [65,72,73].…”
Section: Myeloablation By Irradiation: Mechanisms Side Effects and Amentioning
confidence: 99%
“…Some patients experience mild otitis or transient Eustachian tube dysfunction. A delayed period of fatigue or somnolence following WBRT has been described, particularly in children but also in adults, and may be related to temporary demyelination or inflammatory response [64] [65]. The potential late toxicities of whole brain radiation therapy include an increased risk of cataracts, though the long average latency period to development of radiation-induced cataracts [66] renders this of little importance to the vast majority of patients with brain metastases.…”
Section: Toxicities Of Wbrtmentioning
confidence: 99%
“…Irradiated microglial cells produce a dose-dependent increase of IL-1β, IL-6, IL-18, TnF-α, and IFn-γ-inducible protein-10, which are involved in the process of IR-induced astrocyte gliosis (hwang et al 2006). Pro-inflammatory cytokines such as IL-1β, TnF-α, IL-6, and IL-18 participate in IR somnolence syndrome (Ballesteros-Zebadúa et al 2012). Cytokines induce proteolysis and lipolysis, which are also involved in the cause of malnutrition and cachexia in cancer patients, including IL-1, IL-6, IFn-γ, TnF-α, and brain-derived neurotrophic factor (BDnF) (Katsuramaki et al 1998;Plata-salamán 2000).…”
Section: Roles Of Cytokines In Ir-induced Brain Injurymentioning
confidence: 99%